2017
DOI: 10.1038/s41467-017-00616-2
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of coupled spin–orbit dynamics in cobalt oxide by femtosecond laser pulses

Abstract: Ultrafast control of magnets using femtosecond light pulses attracts interest regarding applications and fundamental physics of magnetism. Antiferromagnets are promising materials with magnon frequencies extending into the terahertz range. Visible or near-infrared light interacts mainly with the electronic orbital angular momentum. In many magnets, however, in particular with iron-group ions, the orbital momentum is almost quenched by the crystal field. Thus, the interaction of magnons with light is hampered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…[44][45][46][47][48]55 We note that magneto-optical coupling of light and spins is frequently used for exciting ultrafast spin dynamics in antiferromagnetic insulators. [29][30][31] However, we found this mechanism to be irrelevant for generating spin photocurrents. 60 We also demonstrated that in the presence of asymmetric Dzyaloshinskii-Moriya interactions it is possible to induce spin photocurrents using linearly polarized light.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[44][45][46][47][48]55 We note that magneto-optical coupling of light and spins is frequently used for exciting ultrafast spin dynamics in antiferromagnetic insulators. [29][30][31] However, we found this mechanism to be irrelevant for generating spin photocurrents. 60 We also demonstrated that in the presence of asymmetric Dzyaloshinskii-Moriya interactions it is possible to induce spin photocurrents using linearly polarized light.…”
Section: Discussionmentioning
confidence: 73%
“…[22][23][24][25] Additionally, a magnonic spin Nernst effect was proposed for quasi-two-dimensional hexagonal antiferromagnets with Dzyaloshinskii-Moriya interactions (DMI) 26,27 and found later experimentally in MnPS 3 . 28 Ultrafast optical excitation of coherent magnon dynamics [29][30][31] is another prominent area, which is in the basic concept of antiferromagnetic optospintronics -a direction targeting optical control of spin states in antiferromagnetic insulators. 32 Although an additional antiferromagnetic layer in a ferromagnet/normal metal interface can sufficiently enhance efficiency of spin pumping, 20,33 and dynamic antiferromagnets can themselves serve as sources of spin currents experiencing a spin backflow from adjacent metal slabs, 34 nonthermal generation of magnon spin currents in bulk antiferromagnets is challenging due to vanishing net magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…In the monochromatic field limit, the fields in Eqs. (7) and (8) and the resulting Poynting vector can be approximated further as explained in Appendix B. This approximation allows us to perform the integrations in Eqs.…”
Section: B Linear Polarizationmentioning
confidence: 99%
“…After this, the integrals over k in Eqs. (7) and (8) can be evaluated analytically leading to the fields given by E p,l (r, t) ≈ Re iω 0 u p,lx + i∂u p,l nk 0 ∂xẑ e i(nk0z−ω0t)…”
Section: Linear Polarizationmentioning
confidence: 99%
“…A key difference between MnF 2 and both α-CoV 3 O 8 and FeF 2 is the presence of strong crystal field effects and spin-orbit coupling in the latter two compounds 133,175 . It is also worth noting that unlike the case of pure CoO 81,91,94,[181][182][183][184] where the large and far reaching exchange constants result in a significant and ultimately problematic entanglement of spin-orbit levels 94 , in the case of α-CoV 3 O 8 , the exchange constants are weak and the Weiss temperature is near 0 K. Both observations suggest that the presence of both strong crystal field effects and spin-orbit coupling with well-separated j eff manifolds, as is the case for α-CoV 3 O 8 , may be central to making the dynamics robust against strong disorder.…”
Section: Comparison Between α-Cov3o8 and Randommentioning
confidence: 99%